PIV Measurement around the Interface of a Falling Droplet - NINOMIYA, Nao; YASUDA, Kazuma; KOBAYASHI, Koichiro (Journal of the Visualization Society of Japan, 2005)
Although the phenomena related to the multiphase flow can be found in many kinds of industrial and engineering applications, the physical mechanism of the multiphase flow has not been investigated in detail. The major reason for the lack of data in the multiphase flow lies in the difficulties in measuring the flow quantities of the multiple phases simultaneously. Presently, the simultaneous visualization and the PIV measurement have been carried out about the both phases of the liquid-liquid two-phase flow. The difference in the refractive indices makes the visualization in the vicinity of the boundary of the multiple phases almost impossible. In this study, the refractive index of the aqueous phase has been equalized to that of the oil phase by adjusting the concentration of aqueous solution. The results show the flow structure both outside and inside of a falling water droplet in the stationary oil simultaneously.